PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR ISLAM AL AZHAR - siskandar, siskandar (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2022)
The development of the Islamic Religious Education (PAI) curriculum in this study contains a discussion of the development of the PAI curriculum in the field of Al-Qur'an tahfizh in Al Azhar Islamic Elementary Schools throughout Jabodetabek. The purpose of this research is to find out 1) Curriculum objectives, 2) implementation process, 3) constraints and challenges, 4) successful strategies for developing the Islamic Religion Education curriculum in the field of Al-Qur'an tahfizh in Al Azhar Islamic Elementary Schools throughout Jabodetabek. The method used in conducting this research is a descriptive analysis method with a qualitative approach where this research is used to analyze and present facts systematically so that they can be more easily understood and concluded. Data collection techniques through interviews, observation guidelines and documentation to obtain information in the form of experiences, attitudes, feelings and ideas of research subjects such as school principals, deputy principals, curriculum areas, Islamic religious education teachers. The results of research on Al Azhar Islamic Elementary School show that Al-Azhar Islamic Elementary School curriculum development refers to the provisions of curriculum development that have been compiled by the PAI curriculum team at the Directorate of Elementary and Secondary Education Islamic Boarding School Foundation (YPI) Al Azhar, but the curriculum development has not been entirely based on the provisions of curriculum development by experts, namely in the form of curriculum documents supplemented by a syllabus, except for Al Azhar Bintaro Islamic Elementary School which already has a more complete tahfizh curriculum document. Obstacle factors in curriculum development are divided into two, namely internal and external factors, which result in the curriculum running less optimally